Peranan PBB dalam Pembentukan Masyarakat Sipil Global - Thontowi, Jawahir (Jurnal Hukum IUS QUIA IUSTUM, 2016)
The ambition of the United Nation to improve its integrity as in international organization indeed much depends on its organizational structure and the already existing leadership models. An attempt to restructure its organization as reflected in the increase of main institution and other related agencies of the United Nations has led the UN functional role in accordance with the goal achievement of the world order and security. Hence, the desire to intensity civil society development has been a vital concern for the United Nation. The process of democratization in the developing countries can fully be delayed.